2019
DOI: 10.1002/aps3.11300
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Chenopodium pallidicaule: An emerging Andean super grain

Abstract: Premise Cañahua is a semi‐domesticated crop grown in high‐altitude regions of the Andes. It is an A‐genome diploid (2n = 2x = 18) relative of the allotetraploid (AABB) Chenopodium quinoa and shares many of its nutritional benefits. Cañahua seed contains a complete protein, a low glycemic index, and offers a wide variety of nutritionally important vitamins and minerals. Methods The reference assembly was developed using a combination of short‐ and long‐read sequencing techniques, including multiple rounds of Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…The genome sequences of the studied species [ Oryza sativa (diploid) [25] , Arabidopsis thaliana (diploid) [26] , Fagopyrum tataricum (diploid) [27] , Beta vulgaris (diploid) [28] , Chenopodium quinoa (allotetraploid) [29] , [30] , Chenopodium pallidicaule (diploid) [29] , [31] , Chenopodium suecicum (diploid) [29] , Daucus carota (diploid) [32] , Lactuca sativa (diploid) [33] , Helianthus annuus (diploid) [34] , Olea europaea (diploid) [35] , Nicotiana attenuata (diploid) [36] , Solanum tuberosum (autotetraploid) [37] , Solanum lycopersicum (diploid) [38] , Actinidia chinensis (heterozygous diploid) [39] , Aquilegia coerulea (diploid) [40] and Amborella trichopoda (diploid) [41] ] were downloaded from the NCBI.…”
Section: Methodsmentioning
confidence: 99%
“…The genome sequences of the studied species [ Oryza sativa (diploid) [25] , Arabidopsis thaliana (diploid) [26] , Fagopyrum tataricum (diploid) [27] , Beta vulgaris (diploid) [28] , Chenopodium quinoa (allotetraploid) [29] , [30] , Chenopodium pallidicaule (diploid) [29] , [31] , Chenopodium suecicum (diploid) [29] , Daucus carota (diploid) [32] , Lactuca sativa (diploid) [33] , Helianthus annuus (diploid) [34] , Olea europaea (diploid) [35] , Nicotiana attenuata (diploid) [36] , Solanum tuberosum (autotetraploid) [37] , Solanum lycopersicum (diploid) [38] , Actinidia chinensis (heterozygous diploid) [39] , Aquilegia coerulea (diploid) [40] and Amborella trichopoda (diploid) [41] ] were downloaded from the NCBI.…”
Section: Methodsmentioning
confidence: 99%
“…It is grown between 3,850 and 4,200 meters above sea level, where frosts are frequent and intense. Kañiwa has an unique nutritional profile, containing 15%–18% of protein, with a balanced essential amino acid composition, including 5%–6% lysine, which is typically limiting in monocotyledonous grain crops (Mangelson et al., 2019; Peñarrieta et al., 2008), as well as micronutrients, such as calcium and iron (Repo‐Carrasco et al., 2003). It is a good source of dietary fiber and other important compounds, such as phenolic compounds, antioxidants, and vitamins and a source of oil with mainly unsaturated fatty acids (Repo‐Carrasco Valencia, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) reported that kañiwa protein is a potential source of bioactive peptides with antioxidant and antihypertensive activity. However, kañiwa has been unknown and underutilized as a food resource outside of the Andes (Mangelson et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The downy mildew in cañahua can be considered a potential threat to the large-scale cultivation of cañahua in the near future. Due to the diploid genome of cañahua (Mangelson et al 2019), it can be used to study the downy mildew disease at molecular level and bene t the whole Chenopodiaceae family.…”
Section: Brief Communicationmentioning
confidence: 99%